Efficacy of Contingency Management for Cocaine Dependence Treatment: A Review of the Evidence - Schierenberg, Alwin; van Amsterdam, Jan; van den Brink, Wim; E. Goudriaan, Anna (Current Drug Abuse Reviews, 2012)
Cocaine dependence causes serious individual and social harm and a considerable proportion of substance related treatment capacity is devoted to cocaine dependent persons. In the absence of approved pharmacotherapies, other treatments for cocaine dependence should be explored. In this review, the efficacy of Contingency Management (CM), a promising behavior therapy using operant conditioning, is evaluated for the treatment of cocaine dependence. A systematic evaluation of 19 studies with a total of 1,664 patients showed that CM - in combination with standard cognitive behavioral or other psychological interventions – (1) increases cocaine abstinence, (2) improves treatment retention during and after group-based or individual psychological treatment, (3) is of benefit in pharmacotherapy trials, and (4) that CM may act synergistically with pharmacotherapy. This suggests that CM is a promising add-on intervention for cocaine dependence treatment. Therefore, it is advocated to include CM in standard treatment programs for cocaine dependence and future pharmacotherapy research. Future larger studies are deemed necessary to replicate these promising results, now often lacking statistical significance.
Keywords: contingency management